Plasmodium falciparum-infected erythrocyte co-culture with the monocyte cell line THP-1 does not trigger production of soluble factors reducing brain microvascular barrier function. - Janet Storm; Grazia Camarda; Michael J Haley; David Brough; Kevin N Couper; Alister G Craig (PLoS ONE)
Monocytes contribute to the pro-inflammatory immune response during the blood stage of a Plasmodium falciparum infection, but their precise role in malaria pathology is not clear. Besides phagocytosis, monocytes are activated by products from P. falciparum infected erythrocytes (IE) and one of the activation pathways is potentially the NLR family pyrin domain containing 3 (NLRP3) inflammasome, a multi-protein complex that leads to the production of interleukin (IL)-1β. In cerebral malaria cases, monocytes accumulate at IE sequestration sites in the brain microvascular and the locally produced IL-1β, or other secreted molecules, could contribute to leakage of the blood-brain barrier. To study the activation of monocytes by IE within the brain microvasculature in an in vitro model, we co-cultured IT4var14 IE and the monocyte cell line THP-1 for 24 hours and determined whether generated soluble molecules affect barrier function of human brain microvascular endothelial cells, measured by real time trans-endothelial electrical resistance. The medium produced after co-culture did not affect endothelial barrier function and similarly no effect was measured after inducing oxidative stress by adding xanthine oxidase to the co-culture. While IL-1β does decrease barrier function, barely any IL-1β was produced in the co- cultures, indicative of a lack of or incomplete THP-1 activation by IE in this co-culture model.